(untitled) (Journal of Bio-Science, 2019)
In the developing countries, stunting has been the most tenacious public health problem and is the major cause of child mortality and global disease burden, where 80% of this burden is found in developing countries and would result in 22% loss of adult income. The aim of this study was to investigate prevalence and determinant factors associated with stunting among pre-school children in Rajshahi City, Bangladesh. A multi-stage cross sectional study was performed during the period March 2017 to September 2017. One thousand and nine (1009) pre-school children (36≤ Age ≤71 months) were considered as our study population. Data were collected by using a pretested and semi-structured questionnaire, which consisted of socio-economic characteristics, dietary and feeding pattern related information. Stunting of a child was determined using the WHO Multicenter Growth Reference Standard. Chi-square test and multiple logistic regressions were carried out to identify determinants of stunting. The odds ratio (OR) with a 95% confidence interval was calculated to assess the strength of the association, and p-value of <0.05 were considered as statistically significant. Boys (52%) with mean age 53.56 ± 10.405 months and girls (48%) with mean age 51.67 ± 10.934 months were participated. The prevalence of stunting among the preschool children in Rajshahi City was 39.7% (5.4% severe, 24.9% moderate and 9.4% mild stunted). The odds of being stunted were illiterate mother, lower food purchasing capabilities, poor dietary diversity score (95% CI: 1.640-3.052; p<0.001), experiencing pre-lacteal (95% CI: 1.616-2.789; p <0.001), prevalence of disease frequency (95% CI: 1.62-3.56; p<0.01), poor socio-economic class (95% CI: 2.83- 9.51; p<0.01). J. bio-sci. 26: 31-40, 2018